Encapsulation of bioactives within electrosprayed κ-carrageenan nanoparticles. (15th October 2022) - Fani, Niloofar; Enayati, M.H.; Rostamabadi, Hadis; Falsafi, Seid Reza
Abstract: In this study, an electrospray synthesis approach was utilized in which a solution mixture of a sensitive bioactive agent, d -limonene (DL, R-(+)-Limonene), and a nature-inspired polymer, κ-carrageenan (κC) was applied to design DL-κC nanoparticles (NPs) in a one step process. The engineered DL-κC NPs displayed spherical morphology and the maximum encapsulation efficiency of NPs was about 97 % by altering the mass ratio of DL to κC. The developed DL-κC NPs showed a pH-dependent release manner in vitro. Both photostability and thermostability of DL were promoted by increasing the κC concentration, and >85 % of the original DL could be preserved following 120 min of UV-light exposure in the NPs with 0.5 % κC. The results demonstrated that electrosprayed κC NPs are promising candidates for the design of high-loading pH-sensitive NPs for encapsulation of highly sensitive bioactive agents. Graphical abstract: Unlabelled Image